The devil's ransom - Taylor, Brad, 1965- (New York : William Morrow, an imprint of HarperCollinsPublishers, 2023)
When his covert company, along with every other entity in the Taskforce, is hit with a ransomware attack linked to the Taliban, Pike must stop a plot to alter the balance of power on the global stage orchestrated by a former NSA specialist in the U.S. government.
Keywords: Logan, Pike -- Fiction; Taliban -- Fiction; Internet and terrorism -- Fiction; Intelligence officers -- Fiction; Action and adventure fiction; Thrillers (Fiction); Spy fiction